2011
DOI: 10.1016/j.jhazmat.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of metoprolol tartrate in suspensions of two TiO2-based photocatalysts with different surface area. Identification of intermediates and proposal of degradation pathways

Abstract: NH . Reaction intermediates were studied in detail and a number of them were identified using LC-MS/MS (ESI+), which allowed the proposal of a tentative pathway for the photocatalytic transformation of MET as a function of the TiO 2 specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 42 publications
(47 reference statements)
5
64
0
Order By: Relevance
“…Among these pharmaceuticals, ␤-blockers are considered emerging contaminants and they are widely used not only in hospitals but also domestically, thus their presence in water bodies is significant. Metoprolol tartrate salt (MET {1- [4-(2-methoxyethyl)phenoxy]-3-(propan-2-ylamino)propan-2-ol tartrate (2:1)}) is one of the most commonly used ␤-blockers for the treatment of variety of cardiovascular diseases, such as hypertension, coronary artery disease, and arrhythmias [12][13][14]. Their presence has been measured in effluents of wastewater treatment plants (WWTP) at concentrations around 730 ng L −1 [15], hospital wastewater (HWW, 417-2232 ng L −1 ) [16] and surface water at concentrations of 2200 ng L −1 [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these pharmaceuticals, ␤-blockers are considered emerging contaminants and they are widely used not only in hospitals but also domestically, thus their presence in water bodies is significant. Metoprolol tartrate salt (MET {1- [4-(2-methoxyethyl)phenoxy]-3-(propan-2-ylamino)propan-2-ol tartrate (2:1)}) is one of the most commonly used ␤-blockers for the treatment of variety of cardiovascular diseases, such as hypertension, coronary artery disease, and arrhythmias [12][13][14]. Their presence has been measured in effluents of wastewater treatment plants (WWTP) at concentrations around 730 ng L −1 [15], hospital wastewater (HWW, 417-2232 ng L −1 ) [16] and surface water at concentrations of 2200 ng L −1 [17].…”
Section: Introductionmentioning
confidence: 99%
“…The advanced oxidation processes (AOPs) have been highlighted, with satisfactory results in the removal of several organic compounds including pharmaceuticals [10,[18][19][20][21][22][23]. Studies have reported the removal of MET by different AOPs, including ozonation [12], UV/H 2 O 2 [24], photo-Fenton [25][26][27], photocatalysis [12,14,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of the plateau, and absence of a significant decrease in the removal efficiency, indicates that the light dissipation at higher catalyst's loading is not pronounced, which is a beneficial characteristic of this catalyst [30].…”
Section: Resultsmentioning
confidence: 95%
“…Photolytic ozonation was also equally effective that of photocatalytic ozonation when using a metoprolol initial concentration of 10 mg/L, this result provides a new way, solar photolytic ozonation for the degradation of emerging contaminants from water. Abramovic et al (2011) investigated the photocatalytic degradation of metoprolol tartrate in suspensions of two TiO 2 -based photocatalysts (Degussa P25 or Wackherr) with different surface area. TiO 2 Wackherr has 6 times less surface area than Degussa P25.…”
Section: Photocatalytic Work On B-blockersmentioning
confidence: 99%